International guide to library and information science education : a reference source for educational programs in the information fields world-wide - Fang, Josephine R.; Nauta, Paul.; Fang, Anna J.; International Federation of Library Associations and Institutions (München ; New York : K.G. Saur, 1985)
This guide is an extremely useful reference work for library and information science education throughout the world.
Includes index.
Includes bibliographical references: p. 522-523.
rpm 24/01/2019
Loans
Keywords: Library education; Library schools; Information science